Crime on Campus: A Survey of Space Users - Robinson, Matthew B. (Crime prevention and community safety, 2001)
This paper reports findings from a study of perceptions and realities of crime at a regional, comprehensive university campus in North Carolina, USA. Specifically, the study explored perceptions of the primary place users of the campus (ie students, faculty, staff, and university police officers) on matters related to criminal victimization, fear of crime, and perception of crime risk. It also assessed environmental conditions on campus. We sought to identify how students, faculty, staff, and police view crime on campus, and to what degree each group feared crime and how they perceived risks to their personal safety. We also aimed to identify environmental conditions unique to particular areas on campus which may be related to fear of crime and perceptions of crime risk. Finally, we compared perceptions of crime on campus with its reality, as measured by self-reported victimizations of students, faculty, and staff, as well as official police reports. Since crime prevention policy on campus is logically best informed by the primary users of campus space, this study sets forth a model for future research in preventing campus crime